Low Body Mass Index of Indigenous Andibila Community Residing at High Altitude in Oju, Nigeria: Who Cares? - Goon, Daniel Ter; Adeniyi, Vincent Oladele; Akusu, Simon Wuhe; Ejeh, Benjamin Ijuo; O. Unogwu, Unogwu (Pakistan Journal of Nutrition, 2017)
Background and Objective: Whilst information is available on the health status of high altitude populations in different regions elsewhere, none exist on the Andibila community, an indigenous population living at high altitude in Oju, Nigeria. This study was conducted to examine the body weight status of the Andibila adults using body mass index to screen for health risk in this population. Materials and Methods: This cross-sectional study involved a convenience sample of 121 Andibila adults residing at high mountain in Oju, Benue state, Nigeria. Anthropometric measurements include weight, height, waist and hip circumferences were determined. Body Mass Index (BMI) (kg m–2) was calculated and utilized as a measure of nutritional status. Results: The mean age of the participants was 49.9±16.5 years. The mean values for BMI, waist circumference, waist-to-hip ratio and waist-to-height ratio were 22.05±11.6, 76.56±15.4, 0.91±0.28 and 0.49±0.1, respectively. The extent of undernutrition (BMI<18.5) was high (23.1%). The prevalence of overweight and obesity was 11.6 and 3.3%, respectively. Conclusion: The high prevalence of underweight among this indigenous, high altitude population requires serious government intervention.